Java mobile agent system - (:unkn) unknown (I O S PRESS, 1998)
This paper presents JMAS (Java Mobile Agent System), a mobile agent environment that is distributed over a network of heterogeneous computers. JMAS is built on top of Java in which an agent can move from one host to another host to perform some service. Its primary task is to provide an environment in which mobile agents can execute. It has JNS (JMAS Name Server) running on a single host, JASs (JMAS Agent Servers) distributed over a network and agent specific user interface programs (Java applets running on web browsers). JMAS Agent (JA) is a Java application class that implements a mobile agent written for a specific problem, such as querying a database, using the JMAS API by a programmer.